Salivary buffering capacity is correlated with umami but not sour taste sensitivity in healthy adult Japanese subjects - Hyodo, Aiko; Mikami, Ayaka; Horie, Kengo; Mitoh, Yoshihiro; Ninomiya, Yuzo; Iida, Seiji; Yoshida, Ryusuke (Archives of oral biology, 2024)
Saliva serves multiple important functions crucial for maintaining a healthy oral and systemic environment. Among them, the pH buffering effect, which is primarily mediated by bicarbonate ions, helps maintain oral homeostasis by neutralizing acidity from ingested foods. Therefore, higher buffering capacity, reflecting the ability to neutralize oral acidity, may influence taste sensitivity, especially for sour taste since it involves sensing H+ ions. This study aims to explore the relationship between salivary buffering capacity and taste sensitivities to the five basic tastes in healthy adult humans. Eighty seven healthy adult students participated in this study. Resting saliva volume was measured using the spitting method. The liquid colorimetric test was used to assess salivary buffering capacity. The whole-mouth taste testing method was employed to determine the recognition threshold for each tastant (NaCl, sucrose, citric acid, quinine-HCl, monosodium glutamate). Taste recognition thresholds for sour taste as well as sweet, salty, and bitter tastes showed no correlation with salivary buffering capacity. Interestingly, a negative relationship was observed between recognition threshold for umami taste and salivary buffering capacity. Furthermore, a positive correlation between salivary buffering capacity and resting saliva volume was observed. Salivary buffering capacity primarily influences sensitivity to umami taste, but not sour and other tastes. •Umami taste showed a negative correlation with salivary buffering capacity.•Other tastes showed no correlation with salivary buffering capacity.•Salivary buffering capacity showed a positive correlation with resting saliva volume.•Taste sensitivity may be affected by the saliva even in healthy adult subjects.